2019
DOI: 10.3389/fonc.2019.00543
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Ongoing Trials of Stereotactic Ablative Radiotherapy for Oligometastatic Cancers: Where Will the Evidence Lead?

Abstract: Purpose: The oligometastatic state is a proposed entity between localized cancer and widely metastatic disease, comprising an intermediate subset of metastatic cancer patients. Most data to support locally-directed treatment, such as stereotactic ablative radiotherapy (SABR), for oligometastases are from retrospective institutional reports. Following the success of a recently completed and reported phase II trial demonstrating important clinical outcomes, herein we review the current landscape of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…18 Ultimately, disease-specific phase 3 RCTs are needed and ongoing. 19 As recently highlighted by the European Society for Radiotherapy and Oncology and European…”
Section: Discussionmentioning
confidence: 97%
“…18 Ultimately, disease-specific phase 3 RCTs are needed and ongoing. 19 As recently highlighted by the European Society for Radiotherapy and Oncology and European…”
Section: Discussionmentioning
confidence: 97%
“…Although randomised phase III evidence is lacking, recent randomised phase II trials have shown the potential of SBRT to improve survival of patients with OMD [9,10,12] and multiple randomized trials are expected in the next few years. A recent review reports 64 ongoing trials studying ablation of OMD, activated and accruing through February 2019 [102]. Over half were phase II (n = 35), however, 17 randomized controlled trials were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Others such as oligorecurrence, -progression and -persistence are plausible scenarios where clinically evident disease may represent the true disease state as opposed to impending wide spread disease. Based on ongoing trials it is clear that further complexity will be added regarding the use of concurrent systemic therapy or immunotherapy [102]. It is therefore critical that authors and editors are explicit about inclusion criteria and definitions, endpoints and toxicity, while continuing to generate evidence on this complex and evolving clinical indication.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of regularly performed staging with CT or positron-emission-tomography (PET)-CT, and the growing recognition of the oligometastatic or oligoprogressive state in different tumor entities, the number of patients presenting with asymptomatic adrenal metastases has increased [32][33][34]. For these patients, surgical resection remains the gold standard, however, many patients are medically unfit for surgery, or their tumors are not technically resectable, and alternative local treatment approaches are required [4,16,35].…”
Section: Discussionmentioning
confidence: 99%